Composite Lightweight Materials with Upgraded Physicochemical Functionality and Improved Economic Feasibility - X. Simos; M. Papageorgiou; I. Kitsou; M. E. Mamasi; T. Gikarakis; A. Ekonomakou; A. Amanatidis; G. N. Anastassakis; A. Tsetsekou (Materials Proceedings)
In recent years, research has revolved around materials with superior functionality. Despite the encouraging results, their commercial use is limited due to high production costs. The major drawback of nanomaterials is their tendency to form aggregates that limit their activity. In order to overcome barriers, the synthesis of advanced, composite materials is proposed. These materials must exhibit high mechanical strength, adhesion between substrate and coating, and enhanced properties when compared to the substrate or the coating. In the present work, expanded perlite substrates were coated or impregnated with materials with a variety of physicochemical characteristics. The influence of the substrate’s physical properties on the performance of the produced composite materials was studied.